Pengaruh ESG terhadap Nilai Perusahaan yang Dimediasi Kinerja Keuangan Perusahaan: Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2022 - Sri Lestari; Prasetiono Prasetiono (Diponegoro Journal of Management, 2025)
This study examines the influence of Environmental, Social, and Governance (ESG) factors on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the mediating role of financial performance. Financial performance is measured using Return on Assets (ROA), while firm value is assessed through the Price to Book Value (PBV) ratio. The research explores how ESG factors contribute to firm valuation and whether financial performance serves as an intermediary in this relationship.The study analyzes manufacturing companies listed on the IDX from 2018 to 2022. Using purposive sampling, 39 companies were selected as the research sample. Panel data regression with logarithmic transformation was employed to minimize heteroscedasticity in the model. The findings reveal that the environmental aspect (ENV) has a positive and significant effect on PBV but a slightly negative impact on ROA. The social aspect (SOC) also positively and significantly affects PBV, while its influence on ROA is minimal and negative. Meanwhile, corporate governance (GOV) does not significantly affect either PBV or ROA.Financial performance (ROA) has a positive and significant effect on PBV but does not mediate the relationship between ENV, SOC, or GOV and PBV. These results indicate that ESG factors, particularly environmental and social aspects, contribute to firm value, but financial performance does not mediate this relationship. This study highlights the importance of ESG considerations in corporate valuation while recognizing the limited mediating role of financial performance.